Words of Intelligence: A Dictionary - Goldman, Jan (Rowman & Littlefield Publishers, 2006)
Words of Intelligence: A Dictionary is intended for the intelligence and national security men and women who are fighting the Global War on Terrorism at all levels: local, state, and federal. The intelligence community has undergone massive changes since the Central Intelligence Agency, National Security Agency, and the Department of Defense were created, and recently, with the establishment of Homeland Security and a Director of National Intelligence, it has taken on even more duties and responsibilities. Intelligence now must be transmitted to state and local public administrators, health officials, and transportation planners (to name just a few) in times of a possible domestic attack. Containing over 600 terms related to theoretical aspects of intelligence, intelligence operations, intelligence strategies, security classification of information, obscure names of intelligence boards and organizations, and homeland security, this dictionary is an invaluable tool for those requiring a working knowledge of intelligence-related issues. A topical index is also included.